Mulla Salih Al-Gozapanki (1394 AH/1974 AD) and his Methodology in his Footnote Called 'Idraak Al-Madarik on Al-Madarik Al-Tanzil and Facts of Interpretation' (Islamic Sciences Journal, 2024)
This research is specialized in the study of the life of Mulla Salih Al- Gozapanki, and his approach through Surat al-Nisa’ to explain the life of the author, and to clarify his approach through his footnote called (Idraak al-Madarik al-Maariq al-Nazil and Facts of Interpretation), as it is one of the valuable comprehensive footnotes to the tasks of footnotes written on the interpretations of al-Kashaf and al-Baydawi.It is to clear  their puzzles, and reveal answers to what is there in the interpretation of Al-Nasafi.  The research began with an introduction to the life of the author and then touched on his approach , showing how to deal with it, supporting all this with examples of interpretation, and then touching on some of the advantages and disadvantages of his interpretation. This research is an excerpt from my MA thesis entitled (Recognition of perceptions of Mulla Salih Al- Gozapanki on (perceptions of revelation and realities of interpretation by Al-Nasafi from verse (24) to verse (87) of Surat Al-Nisa, a study and investigation).This part came as a principle and a conceptual entrance to acknowledge  the author's approach ,  how it is inferred by the hadiths of the Prophet , the sayings of ancient scholars and interpreters,  his exposure to the syntactic, grammatical and rhetorical aspects,  his extraction of jurisprudential and doctrinal deductions and other issues related to the sciences of the Glorious Qura'an.
Keywords: Mullah Saleh Al-QuzaBanki, the curriculum, the footnote to Idraq Al-Madarik, interpretation, the verified text.